North American Culex pipiens and Culex quinquefasciatus are competent vectors for Usutu virus. - Christian L Cook; Yan-Jang S Huang; Amy C Lyons; Barry W Alto; Isik Unlu; Stephen Higgs; Dana L Vanlandingham (Public Library of Science (PLoS), 2018)
BACKGROUND:Usutu virus (USUV) is a member of the Japanese encephalitis virus (JEV) serocomplex in the Flaviviridae family. Emergence of USUV in Europe has led to disease burdens in birds and created increasing concern for the potential zoonotic transmission to humans. Whilst USUV has not been detected in the New World, the identification of competent vector species in North America is critical in the assessment of the likelihood of its dispersal and establishment of enzootic transmission cycles. The objective of this study was to determine vector competence of potential mosquito vectors in North America for USUV. Three medically important mosquito species were selected for testing because of their involvement in the transmission of West Nile virus and St. Louis encephalitis virus, two related JEV serocomplex flaviviruses in the New World. METHODOLOGY/PRINCIPAL FINDINGS:Oral challenge of Culex pipiens, Culex quinquefasciatus, and Aedes albopictus was performed to determine the susceptibility and vector competence of North American mosquitoes for USUV. Infection status was monitored by the isolation of virus from homogenized mosquito tissues. The disseminated form of infection was demonstrated by the detection of infectious virus in the head, wings, and legs of infected mosquitoes. The presence of viral RNA in saliva of infected Cx. pipiens and Cx. quinquefasciatus indicated that both species are competent for transmission of USUV. CONCLUSIONS/SIGNIFICANCE:Results indicate that members of the Cx. pipiens complex are susceptible to USUV and competent for its transmission potential in North America in the event of its introduction. In contrast, Ae. albopictus were highly refractory to USUV infection, suggesting that this species is unlikely to contribute to USUV transmission in North America.